2011
DOI: 10.1371/journal.pone.0020519
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and Comparative Genome Analysis of Two Pathogenic Streptococcus gallolyticus Subspecies: Genome Plasticity, Adaptation and Virulence

Abstract: Streptococcus gallolyticus infections in humans are often associated with bacteremia, infective endocarditis and colon cancers. The disease manifestations are different depending on the subspecies of S. gallolyticus causing the infection. Here, we present the complete genomes of S. gallolyticus ATCC 43143 (biotype I) and S. pasteurianus ATCC 43144 (biotype II.2). The genomic differences between the two biotypes were characterized with comparative genomic analyses. The chromosome of ATCC 43143 and ATCC 43144 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 154 publications
(157 reference statements)
3
45
0
Order By: Relevance
“…Gene clusters containing structural genes for nisin analogues have also been identified in S. gallolyticus subsp. pasteurianus (17,39), S. agalactiae (40), and, most recently, S. suis (18). The gene order in these gene clusters is identical to that for nisin U.…”
Section: Discussionmentioning
confidence: 88%
“…Gene clusters containing structural genes for nisin analogues have also been identified in S. gallolyticus subsp. pasteurianus (17,39), S. agalactiae (40), and, most recently, S. suis (18). The gene order in these gene clusters is identical to that for nisin U.…”
Section: Discussionmentioning
confidence: 88%
“…gallolyticus ATCC 43143 and its close relative S. gallolyticus subs. pasteurianus ATCC 43144 confirmed the common pattern of relative large insertions in the genome encoding environmental and/or virulence factors (Lin et al, 2011b). In this study such regions were identified based on divergence codon adaptation index (CAI), a measure for identification of recently acquired genes (Sharp and Li, 1987).…”
Section: Genomics Of Human and Animal Strainsmentioning
confidence: 90%
“…AP012053.1), and ATCC BAA-2069 (accession no. FR824043) were compared by using the EDGAR software to identify genes they have in common (20)(21)(22)(23). From the resulting gene pool, a set of 22 housekeeping genes were selected on the basis of the variability and length (Ͼ500 bp) of DNA sequences or usage in other MLST schemes.…”
Section: Methodsmentioning
confidence: 99%